2003
DOI: 10.1002/cne.10692
|View full text |Cite
|
Sign up to set email alerts
|

Chronic nerve compression induces concurrent apoptosis and proliferation of Schwann cells

Abstract: Chronic nerve compression (CNC), as in carpal tunnel syndrome, is a common cause of peripheral nerve dysfunction in humans. Previous studies using animal models have demonstrated progressive demyelination and a slowing of nerve conduction velocity. To characterize the Schwann cell response to CNC, we evaluated total Schwann cell number, apoptosis, and proliferation in an animal model of CNC. Design-based stereologic techniques revealed a striking transient increase in Schwann cell number following CNC. Schwann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
143
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 158 publications
(153 citation statements)
references
References 69 publications
(89 reference statements)
9
143
0
1
Order By: Relevance
“…In fact, several studies have reported the importance of mechanical stimuli to the induction of apoptosis. [30][31][32] At T5, important modifications were also noted in the FP which is the second mesenchymal compartment of the hair follicle. FP cells, which originally aligned their major axis parallel to the direction of hair growth, were observed to randomize their orientation, thus losing their cylindrical organization within the bulb (this phenomenon is known in pathology as 'loss of polarity of cells').…”
Section: Mesenchymal Compartmentmentioning
confidence: 99%
“…In fact, several studies have reported the importance of mechanical stimuli to the induction of apoptosis. [30][31][32] At T5, important modifications were also noted in the FP which is the second mesenchymal compartment of the hair follicle. FP cells, which originally aligned their major axis parallel to the direction of hair growth, were observed to randomize their orientation, thus losing their cylindrical organization within the bulb (this phenomenon is known in pathology as 'loss of polarity of cells').…”
Section: Mesenchymal Compartmentmentioning
confidence: 99%
“…23 This phenomenon is similar to our in vivo observation that SCs increase in number within the first 4 weeks of CNC injury. 24 Following 24 hours of hydrostatic compression, there was a 2.6-fold increase in BrdU-labeled SCs compared to control (Fig 5C; control, 1.89 6 0.54%, n ¼ 16; compression, 4.93 6 1.28%, n ¼ 14; p ¼ 0.041). Because a small amount of gas is allowed to escape from the compression chamber during hydrostatic compression, a possible confounding effect of the chamber experiment is an increase in the osmolarity of the culture medium secondary to evaporation.…”
Section: Ultrastructural Characterization Of Biophysical Stimuli-indumentioning
confidence: 89%
“…44,45 Compelling evidence now indicates that SCs play pivotal roles in the pathogenesis of CNC injury, as the CNC-induced SC proliferative response precedes the characteristic demyelination and remyelination response. 24,46 Mechanical loading of SCs alters the expression of genes that permit axonal sprouting, a response observed in later stages of chronic compression injury. 6,47 Our results reported here, colocalizing SCs with the messenger protein Src activated in response to demyelinating biophysical stimuli, further implicate SCs as the prime mediator of CNC injury.…”
Section: Discussionmentioning
confidence: 99%
“…Although neurovascular flow after acute nerve injury has been studied, similar studies after chronic nerve compression injury are limited. Previous studies have shown that such chronic injuries are distinct from acute nerve injuries and have a fundamentally different pathogenesis in which Wallerian degeneration is not seen early after injury 15 . Although axonal pathology and degeneration are absent early after a chronic nerve compression injury, Schwann cells undergo concurrent processes of proliferation and apoptosis 15 .…”
mentioning
confidence: 99%
“…Previous studies have shown that such chronic injuries are distinct from acute nerve injuries and have a fundamentally different pathogenesis in which Wallerian degeneration is not seen early after injury 15 . Although axonal pathology and degeneration are absent early after a chronic nerve compression injury, Schwann cells undergo concurrent processes of proliferation and apoptosis 15 . The compressed nerve has increased vascular permeability and neural vascularity with an upregulation of vascular endothelial growth factor (VEGF) and its Schwann cell receptors (fetal liver kinase receptor and fms-like tyrosine kinase receptor) at early time points, followed by a dramatic decrease [16][17][18] .…”
mentioning
confidence: 99%